The current state and influencing factors of negative social expectations among thyroid cancer patients: a single-center cross-sectional analysis - Wang, Zhitong; Chen, Cui; Lu, Jing; Liu, Zhenfan (Frontiers in Psychology, 2025)
ObjectiveTo investigate the current status and influencing factors of negative social expectations in thyroid cancer patients, aiming to inform interventions that mitigate these expectations and foster positive psychological outcomes.MethodsFrom December 2022 to August 2023, we used convenience sampling to select 213 thyroid cancer patients who met the inclusion and exclusion criteria as research subjects. A questionnaire survey was conducted using a general information questionnaire, the Cancer patient Negative Social Expectation Scale, the simplified version of the psychological Resilience Scale, and the Cancer Loneliness Scale.ResultsThe median negative social expectation score among thyroid cancer patients was 10.00 (IQR: 6.00–17.50), with 31.0% of participants classified as having high negative social expectations. Univariate analysis revealed significant differences in negative social expectation scores across subgroups stratified by age, personality type, marital status, disease type (e.g., papillary vs. non-papillary carcinoma), and Insurance Type (p < 0.05). Correlation analysis demonstrated that the negative social expectation scores were inversely associated with psychological resilience (r =-0.426, p < 0.01) and positively correlated with the loneliness scores (r = 0.651, p < 0.01). Multiple linear regression analysis further identified psychological resilience (β = −0.32, p = 0.003), loneliness (β = 0.51, p < 0.001), disease type (papillary carcinoma vs. others; β = 0.18, p = 0.012), and Insurance Type (β = 0.15, p = 0.023) as significant predictors of negative social expectations, collectively explaining 50.70% of the total variance (R2 = 0.519).ConclusionThe negative social expectations of thyroid cancer patients are at a moderate level. patients with urban resident health insurance, non-papillary carcinoma subtypes, lower psychological resilience scores, and higher loneliness scores exhibited significantly elevated negative social expectation scores. To address this, targeted psychosocial interventions should be implemented for this population. These interventions aim to reduce negative social expectations, facilitate social reintegration, improve quality of life, and alleviate the socioeconomic burden on both families and society.